Mimicking the Annulus Fibrosus Using Electrospun Polyester Blended Scaffolds - Alyah H. Shamsah; Sarah H. Cartmell; Stephen M. Richardson; Lucy A. Bosworth (Nanomaterials, 2019)
Treatments to alleviate chronic lower back pain, caused by intervertebral disc herniation as a consequence of degenerate annulus fibrosus (AF) tissue, fail to provide long-term relief and do not restore tissue structure or function. This study aims to mimic the architecture and mechanical environment of AF tissue using electrospun fiber scaffolds made from synthetic biopolymers-poly(ε-caprolactone) (PCL) and poly(L-lactic) acid (PLLA). Pure polymer and their blends (PCL%:PLLA%; 80:20, 50:50, and 20:80) are studied and material properties-fiber diameter, alignment, % crystallinity, tensile strength, and water contact angle-characterized. Tensile properties of fibers angled at 0°, 30°, and 60° (single layer scaffolds), and ±0°, ±30°, and ±60° (bilayer scaffolds) yield significant differences, with PCL being significantly stiffer with the addition of PLLA, and bilayer scaffolds considerably stronger. Findings suggest PCL:PLLA 50:50 fibers are similar to human AF properties. Furthermore, in vitro culture of AF cells on 50:50 fibers demonstrates attachment and proliferation over seven days. The optimal polymer composition for production of scaffolds that closely mimic AF tissue both structurally, mechanically, and which also support and guide favorable cell phenotype is identified. This study takes a step closer towards successful AF tissue engineering and a long-term treatment for sufferers of chronic back pain.